Measuring project management inputs throughout capital project delivery. Issue 7 (October 2016) - Yun, Sungmin; Choi, Jiyong; Oliveira, Daniel P.; Mulva, Stephen P.; Kang, Youngcheol
Abstract: Despite continuous efforts into benchmarking over the last decades, few have focused on management efforts of project organizations who are involved in managing the capital project. This study presents a phase-based framework and 10 input measures for measuring project management efforts in a capital project. The measures are planning, organizing, leading, controlling, design efficiency, human resources, quality, sustainability, supply chain, and safety. This study quantifies and assesses the inputs and further sorts the results by industry sectors and project phases. The analyses show that traditional functions tend to have more consistent implementation than construction-specific functions. The results indicate that infrastructure sector tends to exert fewer and less consistent efforts than building and industrial sectors. This study contributes a new benchmarking framework and is the first to quantify project management inputs of a capital project systematically. Additionally, phase-focused and phase-wide benchmarking applications of the input measures are also discussed and provided. Highlights: This paper presents a framework for measuring project management efforts throughout capital project delivery. This paper presents 10 input measures representing project management efforts throughout capital project delivery. Linkages between 10 input measures and 120 leading indicators commonly adopted in capital project research are presented. The paper presents phase-focused and phase-wide assessment of project management inputs as benchmarking applications.